2015
DOI: 10.1002/yea.3085
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide screen of fission yeast mutants for sensitivity to 6‐azauracil, an inhibitor of transcriptional elongation

Abstract: Abstract6-Azauracil (6 AU) inhibits enzymes in nucleoside synthesis and depletes the intracellular GTP/UTP pool. Mutations in transcriptional elongation machinery, as well as mutations in a variety of other pathways, exaggerate the growth defect of cells in the presence of 6 AU. Thus, identification of mutations that render cells sensitive to 6 AU will benefit study on the basis of 6 AU-sensitive phenotype. Here we performed a genome-wide screen of a fission yeast deletion library. Of 3235 single-gene deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…From our qualitative sensitivity analysis, the poa1 null strain was sensitive to 6-azauracil, which was presumed to affect elongation in yeast cells by depleting the pools of UTP and GTP and affecting induction of IMD2, which encodes IMP dehydrogenase . Nonetheless, we could not find poa1 from the genome-wide analysis of 6-azauracil-sensitive mutants, but we did find some known poa1 -interacting partners such as nuclear components ccr4 and nab2 . With the use of STRING analysis, Poa1p shows high correlation with the predicted functional partners of HTA1, HTA2, and HTB1 proteins, which are core histone proteins required for chromatin assembly and chromosome function in the nucleus .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…From our qualitative sensitivity analysis, the poa1 null strain was sensitive to 6-azauracil, which was presumed to affect elongation in yeast cells by depleting the pools of UTP and GTP and affecting induction of IMD2, which encodes IMP dehydrogenase . Nonetheless, we could not find poa1 from the genome-wide analysis of 6-azauracil-sensitive mutants, but we did find some known poa1 -interacting partners such as nuclear components ccr4 and nab2 . With the use of STRING analysis, Poa1p shows high correlation with the predicted functional partners of HTA1, HTA2, and HTB1 proteins, which are core histone proteins required for chromatin assembly and chromosome function in the nucleus .…”
Section: Discussionmentioning
confidence: 78%
“…55 Nonetheless, we could not find poa1 from the genome-wide analysis of 6-azauracilsensitive mutants, but we did find some known poa1-interacting partners such as nuclear components ccr4 and nab2. 56 With the use of STRING analysis, Poa1p shows high correlation with the predicted functional partners of HTA1, HTA2, and HTB1 proteins, which are core histone proteins required for chromatin assembly and chromosome function in the nucleus. 57 Accordingly, we used the DeepLoc server 58 for predicting the subcellular localization of Poa1p and found more than 90% probability of Poa1p localized in cytoplasm, with only a few in the nucleus and mitochondria.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…To explore further whether Upf1 has a role in Pol II transcription, we examined whether upf1 Δ cells are hypersensitive to 6-azauracil (6AU). It has previously been reported that strains carrying mutations in components of the RNA polymerase II transcription elongation machinery are hypersensitive to 6AU ( 43 , 44 ). 6AU is an inhibitor of enzymes that are involved in nucleotide biosynthesis; 6AU treatment leads to nucleotide depletion and hence can diminish transcription elongation ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…In view of these changes in Pol II loading and Ser2 phosphorylation, the possibility that Pol II elongation is altered in upf1 Δ cannot be ruled out. Specifically, upf1 Δ shows apparent 6AU hypersensitivity (Figure 7 ), which is a characteristic of transcription elongation S. pombe mutant strains ( 43 ). Additionally, an S. pombe strain carrying a mutant Pol II with reduced elongation rate is also hypersensitive to 6AU ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of 6-azauracil demonstrated that it inhibited the growth of yeast and determined that this was achieved through the inhibition of transcriptional elongation by affecting GTP synthesis and depleting UTP pools . While the literature does not suggest a direct interaction of 6-azauracil with polymerases, studies have demonstrated that uracil can be deleterious if incorporated into DNA .…”
Section: Introductionmentioning
confidence: 99%